Kazalci aktivirane koagulacije pri bolnikih z vensko trombozo in mutacijo v genu za protrombim in faktor V2 - Palusteiner, Katarina (Medicinski razgledi, 2003)
Mutation in the prothrombin gene (G20120A) and in the factor V gene (G1691A), which is manifested as resistance to the activated protein C (nAPC), are important risk factors for thromboembolic disease because they are presumably connected with activated coagulation. The prevalence of both mutations shows asignificant geographical distribution. The prevalence of prothrombin mutationamong patients with deep vein thrombosis is not yet known in Slovenia.The aim of our research was to determine the prevalence of prothrombin gene mutation in patients with deep vein thrombosis and to study the possible connection between this mutation, mutation in factor V and higherconcentrations of markers of activated coagulation: a peptide released from prothrombin during its activation to thrombin (F1+2), a complex between thrombin and antithrombin (TAT) and degradation products of cross-linked fibrin (D-dimers). Our research was based on the hypothesis that the prevalence of prothrombin mutation is similar to that in neighboring populations. Prothrombin mutation and mutation in factor V are connected to higher concentrations of markers of activated coagulation in patients with deep vein thrombosis. 88 patients with deep vein thrombosis were included in the retrospective study. DNA was isolated and DNA analysis was performed. Mutation in the factor V gene was determined as nAPC. The concentrations of markers of activated coagulation were measured using enzyme immunoassays. The prevalence of prothrombin gene mutation was 6.8%, that of nAPC was 23.3% and that of both was 3.5%, which is in concordance with the prevalence of both mutations in patients with deep vein thrombosis in neighboring populations. (Abstract truncated at 2000 characters).
Keywords: Faktor V; Thrombophlebitis; Genetics; Protrombin; Prothrombin; Točkovna mutacija; Tromboflebitis; Factor V; Point Mutation; venska tromboza; koagulacija; geni; mutacije